Effects of lower tiers of government healthcare facilities on unmet need for contraception and contraception use in Bangladesh. - Md Nuruzzaman Khan; Shimlin Jahan Khanam; Md Mostaured Ali Khan; M Mofizul Islam; Melissa L Harris (PLoS ONE, 2023)
Background In low- and middle-income countries (LMICs), including Bangladesh, modern contraception use remains lower than desired, resulting in a higher unmet need. A potential factor contributing to lower contraceptive use is reduced access to and use of lower tiers of government healthcare facilities, including home visits by family welfare assistants (FWAs), as well as women's visits to community and satellite clinics. These relationships, however, are still unexplored in Bangladesh and LMICs more broadly. The aim of this study was to explore the effects of lower tiers of government healthcare facilities on unmet needs for contraception and contraception use in Bangladesh. Methods Data from 17,585 sexually active married women were analyzed from the 2017 Bangladesh Demographic and Health Survey. The outcome variables were any contraceptive use, modern contraceptive use, unmet need for contraception, and unmet need for modern contraception. The explanatory variables considered were respondents' home visits by FWAs, respondents' visits to a community clinic, and respondents' visits to a satellite clinic. Multilevel mixed-effect Poisson regression with robust variance was used to determine the association between the outcome and explanatory variables, adjusted for individual-, household-, and community-level factors. Results Approximately 18% of respondents were visited by FWAs in the three months prior to the survey date and only 3.4% and 3.1% of women attended community and satellite clinics, respectively. Women who reported being visited by FWAs in the three months prior to the survey were approximately 36% less likely to report an unmet need for modern contraception and 42% more likely to report using modern contraception than women who did not report such a visit. A higher likelihood of unmet need for contraception and a lower likelihood of contraception use were found among women who did not visit these community or satellite clinics or visited these clinics for other reasons than collecting contraception as compared to women who visited these clinics to collect contraception. Conclusion Home visits by FWAs to respondents' homes to provide contraception as well as respondents' visits to satellite and community clinics play a major role in Bangladesh to ensure contraception use and reduce the unmet need for contraception. However, their coverage is quite low in Bangladesh. The findings suggest an urgent need for greater government initiatives to increase the number of FWAs and proper monitoring of them at the field level.